Growth hormone for optimization of refractory heart failure treatment - Bocchi,Edimar Alcides (1999)
It has been reported that growth hormone may benefit selected patients with congestive heart failure. A 63-year-old man with refractory congestive heart failure waiting for heart transplantation, depending on intravenous drugs (dobutamine) and presenting with progressive worsening of the clinical status and cachexia, despite standard treatment, received growth hormone replacement (8 units per day) for optimization of congestive heart failure management. Increase in both serum growth hormone levels (from 0.3 to 0.8 mg/l) and serum IGF-1 levels (from 130 to 300ng/ml) was noted, in association with clinical status improvement, better optimization of heart failure treatment and discontinuation of dobutamine infusion. Left ventricular ejection fraction (by MUGA) increased from 13 % to 18 % and to 28 % later, in association with reduction of pulmonary pressures and increase in exercise capacity (rise in peak VO2 to 13.4 and to 16.2ml/kg/min later). The patient was "de-listed" for heart transplantation. Growth hormone may benefit selected patients with refractory heart failure.